International women's tribunal - LC Purchase Collection (Library of Congress) ([Diliman, Quezon City Asianvisions Media Foundation?, 1997)
An international jury of women declared the Philippine government of Cory Aquino guilty of systematic violation of human rights.
Not viewed.
Source used: cataloging record from OvOp field office.
LC Purchase Collection.
Keywords: Documentary